2016
DOI: 10.1007/s00405-016-4111-5
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of low versus high radioiodine administered activity in patients with low-risk differentiated thyroid cancer

Abstract: Post-surgical therapeutic management of differentiated thyroid cancer (DTC) is still a controversial subject. Indeed, there is no consensus on the dose of I to be administered, although the current trend towards therapy easing through mini-cures for patients with good prognosis. To confirm the non-inferiority in terms of effectiveness of an ablative mini-cure from 1.11 to 1.85 GBq, over a cure of 3.7 GBq, in patients with DTC operated for low and very low risk. We retrospectively studied 157 patients with very… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 22 publications
2
6
1
Order By: Relevance
“…Finally, we found that initial recurrence risk and a low-dose ablation were independent predictors for recurrence in our sample. These results are in contrast with those reported by HiLo, where recurrence rates were not associated with RAI ablation strategy [7,8], and also with the results of comparative analyses published to date [9,10]. In this point, it is also interesting to remark that when we took into account only patients with low-risk thyroid cancer, the RAI dose had no relation to recurrence risk, but when we analyzed only patients with intermediate-risk tumours, RAI dose was a strong predictor of recurrence, suggesting that low-dose ablation might be a better strategy in patients with low-risk thyroid cancer than in patients with intermediate-risk tumours.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Finally, we found that initial recurrence risk and a low-dose ablation were independent predictors for recurrence in our sample. These results are in contrast with those reported by HiLo, where recurrence rates were not associated with RAI ablation strategy [7,8], and also with the results of comparative analyses published to date [9,10]. In this point, it is also interesting to remark that when we took into account only patients with low-risk thyroid cancer, the RAI dose had no relation to recurrence risk, but when we analyzed only patients with intermediate-risk tumours, RAI dose was a strong predictor of recurrence, suggesting that low-dose ablation might be a better strategy in patients with low-risk thyroid cancer than in patients with intermediate-risk tumours.…”
Section: Discussioncontrasting
confidence: 99%
“…We found that sTg at the moment of ablation was an independent risk factor for nonexcellent response in the complete sample, but also when we separated patients with low-an intermediate-risk tumours. These results are similar to the results reported by Ghachem et al [9], who found that patients with Tg after surgery <10 ng/mL were more likely to have a complete response, and Fallahi et al, who found that a Tg<4.5 ng/mL was predictive of a complete response [16]. Tg levels after surgery and in RAI ablation have been studied as factors affecting the response to treatment and recurrence rates by many authors [17][18][19][20], and our results seemed to be in the same direction.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations